2013
DOI: 10.1007/s00427-013-0443-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of gene dosage on mandible shape in mice as a model for studying the genetic basis of natural variation

Abstract: Mandible shape in the mouse is a complex trait that is influenced by many genetic factors. However, little is known about the action of single genes on adult mandible shape so far, since most developmentally relevant genes are already required during embryogenesis, i.e. knockouts lead to embryonic death or severe deformations, before the mandible is fully formed. We employ here a geometric morphometrics approach to identify subtle phenotypic differences caused by dosage effects of candidate genes. We use mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…Additional work is needed to connect the observed phenotypic changes to altered gene expression and to pinpoint the timing and sequencing of events leading to abnormal brain morphogenesis. A recent paper found no significant change in mandibular morphometry in Irf6 adult het mice using micro-CT [Boell et al, 2013], although mandibular hypoplasia was observed in knockout embryos [Ingraham et al, 2006]. This suggests that development of the brain is more sensitive to Irf6 dosage than development of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Additional work is needed to connect the observed phenotypic changes to altered gene expression and to pinpoint the timing and sequencing of events leading to abnormal brain morphogenesis. A recent paper found no significant change in mandibular morphometry in Irf6 adult het mice using micro-CT [Boell et al, 2013], although mandibular hypoplasia was observed in knockout embryos [Ingraham et al, 2006]. This suggests that development of the brain is more sensitive to Irf6 dosage than development of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, single-nucleotide polymorphism of NOGGIN has been linked to mandibular hypoplasia (Gutiérrez et al, 2010). In mice, gene dosage of BMP signaling pathway components has been shown to correlate with the size and shape of mandible (Boell et al, 2013). Tissue specific deletion of Bmp4 by Nestin-Cre in craniofacial epithelium and mesenchyme causes cleft lip and inactivation of BmprIa using either Nestin-Cre or Wnt1Cre results in the formation of both cleft lip and cleft palate (Li et al, 2011; Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, this result parallels the realization that most haploinsufficient clinical conditions in human are lesions in transcription factors or other proteins involved with oligomeric complexes [Seidman and Seidman, 2002;Veitia, 2002;Kondrashov and Koonin, 2004]. Gene dosage has an effect on murine phenotypes when mutations in developmental transcriptional regulators are present in a heterozygous state [Boell et al, 2013].…”
Section: Evidence For Genomic Balance and The Inverse Effectmentioning
confidence: 61%